ANALISIS PENGENDALIAN BIAYA PRODUKSI (STUDI KASUS PADA PT. TROPICA COCOPRIMA) - Rotinsulu, Paula C. A.; Saerang, David P.E.; Affandi, Dhullo (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
The movement of the improvement is valued from the capacity of the enterteinment wich can endure in the verry stiff business competition, that is why it needs a good management cost by managing the cost. PT. Tropica Cocoprima is a manufacturing firm producing coconut flour as the final product of the production process that can endure in competition. In the production process activity, the production cost is a factor most influencing in every aspects, and that is why the production cost control measuring standard as the cock of the performance progress of the firm managerial. The goal of this research is to an analyze the efficiency of the controlling production cost at PT. Tropica Cocoprima. By using analysis variance we can get that the cost control is sufficient because it can be categorized over allÂ  favorable. Raw material in November 2012 significantly can be found that the realization of the cost wa Rp. 901/kg, and according to analysis variance was Rp. 30.950.716, at the average of 27,9% and it can be kategorizied as favorable.